map3k1 suppresses terminal differentiation of migratory eye progenitors in planarian regeneration. - Katherine C Lo; Christian P Petersen (PLoS Genetics)
Proper stem cell targeting and differentiation is necessary for regeneration to succeed. In organisms capable of whole body regeneration, considerable progress has been made identifying wound signals initiating this process, but the mechanisms that control the differentiation of progenitors into mature organs are not fully understood. Using the planarian as a model system, we identify a novel function for map3k1, a MAP3K family member possessing both kinase and ubiquitin ligase domains, to negatively regulate terminal differentiation of stem cells during eye regeneration. Inhibition of map3k1 caused the formation of multiple ectopic eyes within the head, but without controlling overall head, brain, or body patterning. By contrast, other known regulators of planarian eye patterning like wnt11-6/wntA and notum also regulate head regionalization, suggesting map3k1 acts distinctly. Consistent with these results, eye resection and regeneration experiments suggest that unlike Wnt signaling perturbation, map3k1 inhibition did not shift the target destination of eye formation in the animal. map3k1(RNAi) ectopic eyes emerged in the regions normally occupied by migratory eye progenitors, and these animals produced a net excess of differentiated eye cells. Furthermore, the formation of ectopic eyes after map3k1 inhibition coincided with an increase to numbers of differentiated eye cells, a decrease in numbers of ovo+ eye progenitors, and also was preceded by eye progenitors prematurely expressing opsin/tyosinase markers of eye cell terminal differentiation. Therefore, map3k1 negatively regulates the process of terminal differentiation within the eye lineage. Similar ectopic eye phenotypes were also observed after inhibition of map2k4, map2k7, jnk, and p38, identifying a putative pathway through which map3k1 prevents differentiation. Together, these results suggest that map3k1 regulates a novel control point in the eye regeneration pathway which suppresses the terminal differentiation of progenitors during their migration to target destinations.